الفكر المقاصدي عند الإمام الجويني وتطبيقاته في مجال الأحوال الشخصية من خلال كتابه (نهاية المطلب في دَراية المذهب) - دوسكي، أمين حجي محمد أمين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study deals with maqasid-oriented of maqasid-based juristic thinking and its application to issues of family jurisprudence and personal status in the work of Imam al-Ḥaramayn al-Juwayni, in his book Nihayat al-Matlab fi Dirayat al-Madhhab, relates to will, marriage and divorce. The researcher has adopted a scientific methodology combining induction, critical analysis and comparison. These three methods have been used either together at the same time separately treated according to the context of the research and the nature of the issues addressed in the different chapters of the study. The inductive method has been used primarily to trace the aspects and cases of maqasid-oriented ratiocination (ta'lil maqasidi), as reflected in al-Juwayni's treatment of the issues belonging to the jurisprudence of family and personal status. Critical analysis has been used mainly to illustrate the conceptual framework of the scientific understanding the objectives of the Shari'ah law according to al-Juwayni and other scholars who contributed to the study of maqasid al-shari'ah. Finally, the comparative method has employed chiefly to relate and contrast al-Juwayni's views on the conceptualization of maqasid and reasoning accordingly with the opinions of other classical scholars before him, after him and his contemporaries. Al-Juwayni did not formulate a technical definition of the idea of maqasid al-shari'ah, but he used explicit terms and clear expressions denoting it; he also laid down its general and fundamental framework expressed by the necessities (daruriyyat), needs (hajiyyat) and embellishments (tahsiniyyat).